PERUBAHAN PARADIGMA UNTUK ATASI KEMISKINAN - Santosa, Purbayu Budi (Fokus Ekonomi, 2006)
Mass poverty is an acute problem experienced by Indonesia. On the other hand, Indonesia itself is well-known for its richness of the natural resources. The shifting of paradigm is necessary to solve the mass poverty problem, from the casual way to act and to think to the extraordinary one. In economics science the casual way to act and to think is reflected in the conventional economic science (orthodox), in which poverty is taken care by providing capital and technical aid. Meanwhile, extraordinary thinking and acting is based on the heterodox economics science in which the analysis of economics is not only based on the factors of economics but also by considering non economic factors. Therefore, capital and technical aid will reach the target whenever the non economic factors become the main consideration on solving poverty problem.Keywords: Paradigm, Poverty, Orthodox Economic Science And Heterodox Economic Science